Okkupatsiia. Misterii . Mistery Occupation - Kudinenko, Andrei (Navigator Film, 2003)
Military drama set in 1942 in Byelorussia. Three intertwined stories about people who made mistakes which could not be repaired. A young peasant Adam, who wants nothing but household happiness, is forced to decide on lives of the others. A mute woman loses her child and tries to save a wounded Nazi instead. A young boy wants to find his father and instead scathes his mother.